Language development as a mechanism linking socioeconomic status to executive functioning development in preschool. Issue 5 (10th January 2022) - Romeo, Rachel R.; Flournoy, John C.; McLaughlin, Katie A.; Lengua, Liliana J.
Abstract: Childhood socioeconomic status (SES) is related to disparities in the development of both language and executive functioning (EF) skills. Emerging evidence suggests that language development may precede and provide necessary scaffolding for EF development in early childhood. The present preregistered study investigates how these skills co‐develop longitudinally in early childhood and whether language development explains the relationship between SES and EF development. A socioeconomically diverse sample of 305 children completed repeated assessments of language (sentence comprehension) and EF (cognitive flexibility, behavioral inhibition, and cognitive inhibition) at four waves spaced 9 months apart from ages 3 to 5 years. Bivariate latent curve models with structured residuals were estimated to disaggregate between‐person and within‐person components of stability and change. Results revealed bidirectional relationships between language and EF across all waves. However, at 3 years, language comprehension more strongly predicted EF than the reverse; yet by 5 years, the bidirectional effects across domains did not significantly differ. Children from higher‐SES backgrounds exhibited higher initial language and EF skills than children from lower‐SES families, though SES was not associated with either rate of growth. Finally, early language‐mediated the association between SES and early EF skills, and this model outperformed a reverse direction mediation. Together, results suggest that EF development is driven by early language development, and that SES disparities in EF are explained, at least in part, by early differences in language comprehension. These findings have implications for early interventions to support children's language skills as a potential pathway to improving early EF development.